Penggunaan Metode Contextual Teaching and Learning (CTL) Pada Pembelajaran Koloid Siswa Kelas XI SMA Katolik Aquino Amurang - Kewo, Klinten S.; Lumingkewas, Sonny; Tuerah, Jeanne M (General Chemistry Journal, 2023)
hemistry is reality-dependent information and the results of exploration directed by specialists. Chemistry is not static, but creative in accordance with the development of science and innovation (science and technology). Some high school students find chemistry a very challenging subject. Thus, educators of this subject are required to have the choice to provide chemistry in an interesting and inventive way. The reason for this research is to decide on the use of Context Oriented Teaching and Learning (CTL) techniques in colloid learning for XI grade students of Aquino Amurang Catholic High School. Collecting information in this study using colloid test questions given to 18 students. Then, at that time it was broken down to determine the dominance of student learning by using the classification of high, medium, low, and very low evaluations. From the results of the investigation, information on the main pattern of the number of students who got high scores was 6 students and 12 students were moderate. In the second cycle, the number of students who got high scores was 7 students and 11 students were moderate.